Syntactic analysis of the project-based learning model in the Waskitha Basa Lan Sastra Jawa textbook for grade x senior and Islamic high schools - Octaviani, Lisa; Mujimin, Mujimin (Asatiza: Jurnal Pendidikan, 2025)
Learning models play a critical role in the educational process. They are systematically designed as a guide for conducting learning activities to achieve educational objectives. Each learning model includes specific syntax that can be implemented by students under teacher guidance. This study aims to analyze the syntax of learning models based on the learning activities presented in the textbook published by Erlangga, titled Waskitha Basa lan Sastra Jawa for Grade X Senior and Islamic High Schools. The study employs a descriptive qualitative research method with observation and interactive analysis. The research instrument consists of data cards. The data analysis technique used is content analysis. The results of the study reveal that the Waskitha Basa lan Sastra Jawa textbook for Grade X, which consists of six chapters, includes four chapters (Chapters 1, 2, 3, and 4) that apply the Project-Based Learning model. However, two chapters (Chapters 5 and 6) were found not to implement any discernible learning model. This research provides valuable insights for textbook authors to ensure the completeness of the learning model syntax applied in textbooks. Consequently, the learning process facilitated by the textbook can be optimized and aligned with the intended learning model syntax to effectively achieve educational goals.